Creative tourism and sustainable territories : insights from Southern Europe - Remoaldo, Paula Cristina A.; Alves, Juliana; Ribeiro, Vítor (Emerald Publishing Limited, 2022)
Creative Tourism and Sustainable Territories: Insights from Southern Europe examines the growth and development of this emerging and fast developing area of tourism practice, while assessing it's impacts on sustainability and regional development. Examples are drawn from across Southern Europe with analysis of Creative Tourism practices in Portugal, Italy, Spain, Greece, Croatia, Serbia, Montenegro, and Slovenia. Creative Tourism and Sustainable Territories features chapters from leading scholars that explore the definition and evolution of Creative Tourism, the roles played by urban and rural territories, the motivations and profiles of a creative tourist, best practices in Creative Tourism and contribution of festivals to Creative Tourism and territorial development providing an expansive study that will be of interest to researchers in Tourism Studies, Hospitality Studies, Sustainability, Economic Development and Cultural Industries, and Geography.
Keywords: Tourism -- Europe, Southern.; Business & Economics -- Industries -- Hospitality, Travel & Tourism.; Tourism industry.; elektronické knihy; electronic books